AN ANALYSIS ON MURABAHAH APPLIED IN BANK TABUNGAN NEGARA (BTN) SYARIAH MALANG BRANCH - HIDAYATI, BARIDA (IQTISHODUNA, 2007)
This research is based on the good performance of murabahah financing on Indonesia Islamic Banking. The murabahah is one of the financing products that based on the Islamic trading principle which is preeminence the honest between the seller and the buyer. According to it, this research investigates the transparency process in BTN Syariah including the transparency pre-akad, akad and after akad. This research is designed using qualitative method. To collect the data the researcher uses interview, observation and documentation, while for verifying data the researcher uses triangulation. The result of this research explains that murabahah transparency is done well in BTN Syariah Malang Branch, even it is found many problem on it. The problem found is identified on pre akad, on akad and before akad. the problem on pre akad is found around the bank explanation and the client understanding, the akad problem is found around the akad reading and the akad signing while the after akad problem is found around the accelerate payment formula.